Enhancing library services via technology: in-house development of an online library booking system - Amno, Hasniza; Abdul Jais, Nurulhuda; Ismail, Ida Shazrina; Amin Azmi, Muhamad (Universiti Teknologi Mara, Kedah, 2023)
The Library Tech Tool Online Booking (LTTOB) is an online library booking system for equipment, tools, or devices available at the IPPT Library for all Universiti Sains Malaysia (USM) members. The primary function of this system is to allow library users to make reservations and facilitate staff in managing those bookings. Access to the LTTOB system is granted through the "Identiti@USM" login. LTTOB streamlines the user booking process, starting from the application, checking the reservation status, and concluding with the completion of the booking. Equipped with availability schedules, locations, and space statuses displayed on the main menu, it simplifies user decision-making. A green indicator signifies available spaces and devices, while pink indicates a space has been filled or reserved. This user-centric LTTOB system is user-friendly and easily managed by library staff. The system's features allow each device and tool to be set according to different time slots and locations. Staff can make adjustments, amendments, or temporary blocks to the slots and dates indicated in the provided schedule grid. Booking statistics can be generated through the LTTOB system for analysis reports and monitoring purposes. In essence, this system's development streamlines processes for staff and users. The LTTOB system is a user-friendly application that aids in monitoring services and is easy to use. It greatly assists the library in providing a customer-friendly experience while facilitating effective service monitoring.